PROPERTIES OF THE SUBGIANTS IN THE ECLIPSING BINARY SYSTEMS OF DIFFERENT TYPES - Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
The properties of subgiants from eclipsing binary systems are considered. The necessity of their dividing into different groups on masses and orbital periods is suggested. It allows to find the significant correlations between the main characteristics of supergiants and the corresponding systems’ characteristics. It is shown that low-mass subgiants from short-period systems quickly lose the mass. They possess the largest temperature and radii excesses, but with mass and period increasing the temperature excesses are replaced by the temperature deficiency, which are maximal for massive subgiants of AR-systems.